Devonian Jinshuikou pegmatites at the northern margin of the Tibetan Plateau: UPb and SmNd constraints on their genetic relationship with regional granitoids - Si-Qi Liu; Shao-Yong Jiang; Mostafa Fayek; Hui-Min Su; Yu-Ying Che; Wei Wang; Qinglin Xia (Lithos, 2026)

Chlorpyrifos exposure induces inflammatory and immune dysregulation: An integrative in silico and in vitro analysis - Chen-Yu Chiang; Shih-Pin Chen; Ci-Wen Luo; Chun-Hung Su; Shiuan-Shinn Lee; Wen-Ying Chen; Chun-Jung Chen; Ching-Chi Tseng; Pin-Tzu Chen; Yin-Che Lu; Yu-Hsiang Kuan (Pesticide Biochemistry and Physiology, 2026)

Energy-efficient dynamic control of carbon capture for hot blast stoves: A physics-constrained and surrogate-based framework - Sihong Cheng; Zichang Che; Wenbo Zhang; Yi Xing; Wei Su; Tao Yue (Fuel, 2026)

Steam-assisted dry reforming of methane over a Ce-doped Ni/calcium aluminate catalyst enabling stable syngas production - Ding Wang; Jiming Liu; Yuchen Che; Hao Yang; Bohao Li; Tong Su; Jinhong Zhang (Fuel, 2026)

Coastal bathymetry extraction from ICESat-2 using an elliptical neighborhood clustering algorithm with adaptive size and direction - Junyu Che; Chao Qi; Huadong Ma; Huiying Zheng; Dianpeng Su; Hans-Gerd Maas; Fanlin Yang (Marine Geodesy, 2026)

Integrated transcriptomic and metabolomic analyses elucidate the molecular mechanisms underlying quality formation during Rosa acicularis fruit ripening - Wuhua Zhang; Yuli Zhou; Yuexi Du; Man Su; Ziqing Xie; Shuai Li; Jie Dong; Naiyu Zhang; Jiani Duan; DaiDi Che; Aimin Zhou; Jinzhu Zhang; et al. (Food Research International, 2026)

Structure-dependent inhibition of human carboxylesterase 1 by organophosphate esters: integrated in vitro profiling and 3D-QSAR interpretation - Zhuohua Cao; Siyu Men; Zhenhua Li; Gang Liu; Qingying Su; Xinran Chen; Xianhua Che; Hanyong Jin (Chemico-Biological Interactions, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Research progress on preparing CO2 adsorbents from waste materials - Yingzhe Shi; Ximiao Liu; Hualong Zhou; Wentao Guo; Zichang Che; Wei Su; Yi Xing (Journal of Environmental Chemical Engineering, 2026)

Using ChatGPT to Solve Clinical Radiobiology Problems - Che-Wei Su; Kun-Yao Dai; Yu-Jen Chen; Yung-Shuo Kao (Journal of Cancer Education, 2026)

Influence of free surface on microwave-induced rock fracturing: An experimental and numerical study - Yanlong Zheng; Ziqiang Su; Gaofeng Zhao; Ping Che; Jianchun Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

Shionone ameliorates pulmonary fibrosis by activating mitophagy via PINK1-Parkin pathway - Yijia Su; Qiang Fu; Xilin Wu; Xianhua Che; Zhe Jiang; Xuezheng Li (Toxicology and Applied Pharmacology, 2026)

Structural and functional study of clay heterostructures induced by amine carbon chain - Muhammad Kashif; Alireza Ranjbari; Alireza Pourvahabi Anbari; Clovis Awah Che; Tatwadhika Rangin Siddhartha; Yaxin Su; Philippe M. Heynderickx (Journal of Environmental Chemical Engineering, 2026)

High-transparent and mechanically robust self-polishing coatings reinforced by hyperbranched nanocellulose for marine biofouling resistance - Zhongshuai Gao; Linfei Ma; Mingda Che; Cunguo Lin; Mei Cui; Rongxin Su; Renliang Huang (Carbohydrate Polymers, 2026)

Numerical prediction of progressive failure in earthquake-damaged slopes under rainfall using MPM - Chao Su; Ailan Che; Ganglie Yuan; Hanxu Zhou; Xiaowei Li (Landslides, 2026)

Engineering odor control in algal foods: Machine learning for quality enhancement - Yilan Sun; Qinhua Zhang; Hongkun Lin; Juehan Lu; Huiyue Zhang; Che Su; Shiguo Huang; Jie Pang; Xiaolin Li (Journal of Food Engineering, 2026)

Boosting catalytic activity toward industrial water electrolysis: Ag–triggered dual–site activation in NiFe LDH for ultra–efficient oxygen evolution reaction - Habib Gemechu Edao; Chia-Yu Chang; Woldesenbet Bafe Dilebo; Chemeda Barasa Guta; Keseven Lakshmanan; Endalkachew Asefa Moges; Fikiru Temesgen Angerasa; Baru Debtera Bejena; Chun-Chi Chang; Wei-Sheng Liao; Meng-Che Tsai; Wei-Nien Su; et al. (Chemical Engineering Journal, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Inhibitory regulation of glutamate release from rat cortical nerve terminals by thymoquinone - Mao-Hsiang Hsiao; Kun‑Chieh Yeh; Ming-Yi Lee; Wei-Che Chiu; Su-Jane Wang (NeuroToxicology, 2025)

Machine learning-enhanced meta-analysis unravels the global patterns of microplastic-heavy metal co-toxicity in terrestrial ecosystems - Hai-han Jiang; Tian-Hao Che; Qing Su; Bin Jin; Yan Lu; Han-Xi Zhou; Min-Jie Fu; Jing-Ya Zhou (Environmental Pollution, 2025)

Novel insight into the heavy metal immobilization by coal fly ash-based geopolymers using machine learning and density functional theory - Kaizhi Yang; Bo Yang; Kezhou Yan; Yining Su; Longyi Zhao; Jungang Tang; Yu Che; Yanxia Guo (Waste Management, 2025)

Decisive electrocatalyst of oxyphilic transition metals with bivalent metal perovskites: Localized oxygen confinement for enhanced 2e-WOR in H₂O₂ production - Chemeda Barasa Guta; Chia-Yu Chang; Fikiru Temesgen Angerasa; Baru Debtera Bejena; Habib Gemechu Edao; Woldesenbet Bafe Dilebo; Endalkachew Asefa Moges; Meng-Che Tsai; Wei-Nien Su; Bing Joe Hwang (Chemical Engineering Journal, 2025)

Urinary phthalate metabolites associate with blood levels of estrogen quinone-derived hemoglobin adducts in Taiwanese pregnant women - Shu-Li Wang; Dar-Ren Chen; Sheng-Yen Hsu; Chia-Wei Liu; Che Lin; Chien-Wen Sun; Pen-Hua Su; Ying-Chih Tseng; Po-Hsiung Lin (Toxicology Letters, 2025)

Carbon-water nexus of China's iron and steel industry through CCUS technology development - Wei Su; Ximiao Liu; Jinglei Tian; Saige Wang; Yi Xing; Zichang Che; Juan Liu (Journal of Cleaner Production, 2025)

Origin and Geological Significance of the Cambrian–Permian Mafic-Felsic Magmatic Rocks in the Longshenggeng Area of the East Kunlun Orogenic Belt - Hua Li; Hui-Min Su; Haikui Tong; Changhai Luo; Jianxin Zhang; Tao Wang; Wenjun Li; Chaoping Xue; Jiaxiang Dong; Yuying Che; Xiaolin Chen; Xiong Li (Journal of Earth Science, 2025)

Gaining water bodies by climate change benefits water crisis mitigation in central Asia - Yanan Su; Shengqian Chen; Yijie Sui; Xin Li; Jinhao Xu; Xianghong Che; Tingting Xie; Jianhui Chen; Yongwei Sheng; Min Feng; Fahu Chen (Science Bulletin, 2025)

Mechanisms of corrosion and corrosion scale formation in water supply networks: A review - Qunfang Hu; Jiahua Zhou; Zhan Su; Shuang Nie; Fei Wang; Zongyuan Zhang; Qiang Zhang; Delu Che (Journal of Water Process Engineering, 2025)

Research progress and future trends in smart response packaging for food preservation - Xiaowei Xu; Hanbin Chen; Qin Wang; Che Su; Yilan Sun; Chao Qiu; Jie Pang (Journal of Stored Products Research, 2025)

Single-step pyrolytic synthesis of ultra-microporous ammonialized biochar for carbon dioxide capture - Che-Jung Hsu; I-Lin Kuo; Hsing-Cheng Hsi; Su Shiung Lam; Ying-Pin Huang; Yu-Chieh Ting (Journal of Environmental Management, 2025)

Research progress and future prospects of chemical utilization of CO2 - Yingzhe Shi; Wei Su; Yi Xing; Yongkang Cui; Ximiao Liu; Wentao Guo; Zichang Che (Chemical Engineering Journal, 2025)

Protecting mud crabs from pollution by microplastics, per- and polyfluoroalkyl substances, polycyclic aromatic hydrocarbons, pesticides, and heavy metals in mangroves - Wan Adibah Wan Mahari; Yiu Fai Tsang; Che-Jung Hsu; Hanafiah Fazhan; Youji Wang; Kianann Tan; Rock Keey Liew; Cheng-Di Dong; Khor Waiho; Su Shiung Lam (Environmental Chemistry Letters, 2025)

Molecular characterization of TRAF gene family in snakehead (Channa argus) - Xiu Feng Han; Ming Yue Che; Xue Su; Jing Yun Tian; Lan Hao Liu; Pin Nie; Su Wang (Fish & Shellfish Immunology, 2025)

Analysis on the failure mechanism and entire evolution process of toppling bank slope under heavy rainfall utilizing material point method - Chao Su; Ailan Che; Jifang Zhou; Guoquan Xie (Engineering Geology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A unit series–parallel unsaturated soil electrical conductivity model considering interconnections between pores - Ganglie Yuan; Ailan Che; Chao Su (Journal of Hydrology, 2025)

Ticks jump in a warmer world: Global distribution shifts of main pathogenic ticks are associated with future climate change - Bo Cao; Chengke Bai; Kunyi Wu; Ting La; Wenwen Chen; Lianjin Liu; Xiaofang Zhou; Chong Chen; Xian Li; Yiyang Su; Lingyu Che; Guishuang Li (Journal of Environmental Management, 2025)

Tandem synergetic effect in symbiotic Co catalyst for enhanced oxygen reduction - Jing Zhang; Meihuan Liu; Yuhao Zhang; Hui Su; Xiuxiu Zhang; Baojie Li; Jianglong Guo; Youcai Che; Weiren Cheng; Qinghua Liu (Chemical Engineering Journal, 2025)

Trifunctional surface engineering of Lithium-rich manganese-based oxides via Al3+/PO43− co-doping and oxygen vacancy regulation for High-performance lithium-ion batteries - Hongyun Zhang; Jinyang Dong; Gang Chen; Huiquan Che; Kang Yan; Xi Wang; Jinzhong Liu; Dewang Liu; Yun Lu; Ning Li; Yuefeng Su; Feng Wu; et al. (Chemical Engineering Journal, 2025)

Mechanical properties and interfacial adhesion mechanism of polyolefin composites reinforced with ethylene vinyl alcohol-coated cellulose microfibers - Yixin Zhao; Shuya Zhang; Lei Zhang; Mingda Che; Renliang Huang; Mei Cui; Wei Qi; Rongxin Su (Chemical Engineering Journal, 2025)

Triple modifications of Li-rich manganese-based cathode materials using LiMnPO4 one-step method - Jianan Hao; Jinyang Dong; Yuefeng Su; Kang Yan; Jiayu Zhao; Huiquan Che; Yun Lu; Ning Li; Bin Zhang; Ping Zhang; Feng Wu; Lai Chen (Chemical Engineering Journal, 2025)

A Kirkendall strategy for the efficient degradation of trichloroethylene from groundwater using cellulose nanofiber-supported sulfidated nZVI - Mingda Che; Jingzhe Xiao; Shuya Zhang; Cancan Shan; Ze Zhao; Renliang Huang; Yitong Zhou; Mei Cui; Wei Qi; Rongxin Su (Chemical Engineering Journal, 2024)

Establishment and Validation of Sandell-Kolthoff Method for Saliva Iodine Determination - Yue Su; Ming Li; Honglei Xie; Xin Hou; Meng Zhao; Jia Li; Haowen Pan; Zexu Zhang; Zongyu Yue; Wenjing Che; Lanchun Liu; Jiasen Cao; et al. (Biological Trace Element Research, 2024)

Fluorinated Polyimides incorporated with heterogeneous ZrO2@KNbO3 as multiple carrier transport barriers for Ultra-High energy storage - Yao Su; Yuxin Jia; Dengwei Hu; Shilei Zhu; Xin Yang; Xiuzi Che; Yuanbiao Gong; Yongbo Fan; Weijia Wang; Huiqing Fan (Chemical Engineering Journal, 2024)

Chemical regulation of lignin spatial conformation for a multifunctional soft material with a novel energy dissipation mechanism - Yingying Su; Xiao Han; Guanda Che; Jinghui Zhou; Yao Li; Sheng Cheng; Cong Wang; Xu Fei (Chemical Engineering Journal, 2024)

Novel electrocatalyst with abundant oxygen vacancies enabling efficient two-electron water oxidation reaction for H2O2 synthesis - Chemeda Barasa Guta; Habib Gemechu Edao; Woldesenbet Bafe Dilebo; Chia-Yu Chang; Fikiru Temesgen Angerasa; Endalkachew Asefa Moges; Yosef Nikodimos; Keseven Lakshmanan; Meng-Che Tsai; Wei-Nien Su; Bing Joe Hwang (Chemical Engineering Journal, 2024)

Nanopolystyrene and phoxim pollution: A threat to hepatopancreas toxicity in Chinese mitten crab (Eriocheir sinensis) - Mengting Huang; Yuan Ma; Shunli Che; Longteng Shen; Zhicheng Wan; Shiping Su; Shuquan Ding; Xilei Li (Aquatic Toxicology, 2024)

Targeting TGFβ receptor-mediated snail and twist: WSG, a polysaccharide from Ganoderma lucidum, and it-based dissolvable microneedle patch suppress melanoma cells - Hung-Chih Lo; Tzu-En Lin; Che-Yu Lin; Wei-Hao Wang; Yu-Chen Chen; Pei-Hsien Tsai; Jung-Chen Su; Mei-Kuang Lu; Wei-Hung Hsu; Tung-Yi Lin (Carbohydrate Polymers, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Mechanical behavior of immersed tunnel under the influence of differential settlements: A case study of GZ tunnel - Chao Su; Ailan Che; Ziyao Xu; Zhaolong Han; Feng Zhu; Tong Hai (Tunnelling and Underground Space Technology, 2024)

Whole-genome resequencing highlights the phycosphere microbial network in global populations of the edible kelp Undaria pinnatifida - Jihoon Jo; Hyun Hee Hong; Louis Graf; Che Ok Jeon; Hwan Su Yoon (Algal Research, 2024)

Silicate melt immiscibility as the cause of large-scale rare-metal mineralization in a peralkaline granite system: The case of the Baerzhe deposit in NE China - Hui-Min Su; Shao-Yong Jiang; Tao Jin; Yu-Ying Che; Xin-You Zhu (Lithos, 2024)

Metabolic relationships between marine red algae and algae-associated bacteria - Kyung Hyun Kim; Jeong Min Kim; Ju Hye Baek; Sang Eun Jeong; Hocheol Kim; Hwan Su Yoon; Che Ok Jeon (Marine Life Science & Technology, 2024)
Mutualistic interactions between marine phototrophs and associated bacteria are an important strategy for their successful survival in the ocean, but little is known about their metabolic relationships. Here, bacterial communities in the algal sphere (AS) and bulk solution (BS) of nine marine red algal cultures were analyzed, and Roseibium and Phycisphaera were identified significantly more abundantly in AS than in BS. The metabolic features of Roseibium RMAR6-6 (isolated and genome-sequenced), Phycisphaera MAG 12 (obtained by metagenomic sequencing), and a marine red alga, Porphyridium purpureum CCMP1328 (from GenBank), were analyzed bioinformatically. RMAR6-6 has the genetic capability to fix nitrogen and produce B vitamins (B1, B2, B5, B6, B9, and B12), bacterioferritin, dimethylsulfoniopropionate (DMSP), and phenylacetate that may enhance algal growth, whereas MAG 12 may have a limited metabolic capability, not producing vitamins B9 and B12, DMSP, phenylacetate, and siderophores, but with the ability to produce bacitracin, possibly modulating algal microbiome. P . purpureum CCMP1328 lacks the genetic capability to fix nitrogen and produce vitamin B12, DMSP, phenylacetate, and siderophore. It was shown that the nitrogen-fixing ability of RMAR6-6 promoted the growth of P . purpureum , and DMSP reduced the oxidative stress of P . purpureum . The metabolic interactions between strain RMAR6-6 and P . purpureum CCMP1328 were also investigated by the transcriptomic analyses of their monoculture and co-culture. Taken together, potential metabolic relationships between Roseibium and P . purpureum were proposed. This study provides a better understanding of the metabolic relationships between marine algae and algae-associated bacteria for successful growth.

Nutrients addition decreases soil fungal diversity and alters fungal guilds and co-occurrence networks in a semi-arid grassland in northern China - Hongling Yang; Li Cheng; Limuge Che; YongZhong Su; Yulin Li (Science of The Total Environment, 2024)

Enhanced extraction of heavy metals from gypsum-based hazardous waste by nanoscale sulfuric acid film at ambient conditions - Wenjing Li; Chunli Wang; Guiquan Che; Min Su; Zhihao Zhang; Weizhen Liu; Zhang Lin; Jing Zhang (Journal of Hazardous Materials, 2024)

Nitrate denitrification rate response to temperature gradient change during river bank infiltration - Yazhi Song; Xisosi Su; Qiaohui Che; Weihong Dong; Yuyu Wan; Hang Lyu; Tiejun Song (Environmental Geochemistry and Health, 2024)

Adsorption and accumulation of N2 at the solid–liquid interface: The impact of hydration films - Bao Li; Dan Su; Daochang Che; Lei Zhang; Shengyu Liu; Boris Albijanic (Minerals Engineering, 2024)

Adsorption and enrichment of low-concentration heavy metal complexes by retractable claws made of polyelectrolyte brushes - Guiquan Che; Zhihao Zhang; Wenjing Li; Min Su; Chunli Wang; Zhengping Hao; Jing Zhang (Chemical Engineering Journal, 2024)

Water pollution scenarios and response options for China - Haoyuan Feng; Joep F. Schyns; Maarten S. Krol; Mengjie Yang; Han Su; Yaoyi Liu; Yongpeng Lv; Xuebin Zhang; Kai Yang; Yue Che (Science of The Total Environment, 2024)

Enhanced microalgal biomass and lipid production with simultaneous effective removal of Cd using algae-bacteria-activated carbon consortium added with organic carbon source - Jianke Huang; Bocheng Su; Xingyi Fei; Jiayi Che; Ting Yao; Ruizeng Zhang; Sanjiong Yi (Chemosphere, 2024)

Responses of radial growth to climate change for two dominant artificial coniferous trees - Jingrong Su; Shengchun Xiao; Xiaomei Peng; Cunwei Che; Peng Zhao (Dendrochronologia, 2024)

Efficient composite chlorinated ethenes removal using gallic acid to enhance Fe/Ni nanoparticles activated persulfate - Mingda Che; Hongjian Su; Huimin Si; Bin Guo; Renliang Huang; Jing Zhao; Rongxin Su (Environmental Science and Pollution Research, 2024)

Structure-specific metabolism of flavonol molecules by Bacillus subtilis var. natto BCRC 80517 - Che-Wei Wang; Hsin-Ya Tsai; Chen Hsu; Ching-Chun Hsieh; I-Shu Wang; Chi-Fon Chang; Nan-Wei Su (Food Chemistry, 2024)

Enhancing Viability of Human Embryonic Stem Cells during Cryopreservation via RGD-REP-Mediated Activation of FAK/AKT/FoxO3a Signaling Pathway - Jeong Hee Kim; Jeong In Choi; Young Hyun Che; Su Haeng Sung; Hojae Lee; Sun Lee; Jae-Hoon Park; Yun-Il Lee; Young-Sam Lee; Won Bae Jeon; Yong Jun Kim (Tissue Engineering and Regenerative Medicine, 2023)

Study on the Mechanism of Eerdun Wurile’s Effects on Post-operative Cognitive Dysfunction by the TLR4/NF-κB Pathway - Yun Qiao; Huiru Li; Yan Li; Enboer Su; Zhe Wang; Limuge Che; Yiri Du (Molecular Neurobiology, 2023)
The object of our work was to observe whether the Mongolian medicine Eerdun Wurile (EW) improve postoperative cognitive dysfunction (POCD) by affecting the TLR4/NF-κB. Mice (6–8-week-old male C57BL/6 J) were selected to establish an animal model of POCD by combining intracerebroventricular injection of lipopolysaccharide and nephrectomy; EW formulation and EW basic formulation were administered intra-gastrically for 7 consecutive days. The cognitive performance was assessed by Morris water maze test. H&E staining was examined to detect alterations in hippocampal tissue. Immunohistochemical staining was performed to evaluate MyD88, NF-κB, TLR4, iNOS, and IBA-1 expressions; Western blotting and RT-qPCR were performed to evaluate MyD88, NF-κB, and TLR4. The expressions of IL-6, IL-1β, and TNF-α were evaluated by ELISA. Intracerebroventricular injection of lipopolysaccharide combined with nephrectomy induced cognitive dysfunction in mice, stimulated TLR4/NF-κB and microglia, and promoted the secretion of murine TNF-α, IL-1β, and IL-6. EW formulation and EW basic formulation treatment are able to suppress the TLR4/NF-κB pathway activation and microglia, and the serum cytokine secretions related to proinflammation, and restore the cognitive performance. EW formulation and EW basic formulation can improve POCD in mice, and TLR4/NF-κB pathway seems to be one of the important mechanisms in EW’s improvement of POCD.

Organohydrogels with cellulose nanofibers enhanced supramolecular interactions toward high performance self-adhesive sensing pads - Cancan Shan; Lukas Bauman; Mingda Che; A-Reum Kim; Rongxin Su; Boxin Zhao (Carbohydrate Polymers, 2023)

Tannic acid enhanced the removal of Phaeocystis globosa from seawater by Fe (II) activated persulfate - Mingda Che; Xianfeng Wang; Mei Cui; Renliang Huang; Wei Qi; Rongxin Su (Journal of Environmental Chemical Engineering, 2023)

Piperlongumine induces apoptosis and autophagy via the PI3K/Akt/mTOR pathway in KB human cervical cancer cells - Eun-Ji Han; Eun-Young Choi; Su-Ji Jeon; Sang-Woo Lee; Jun-Mo Moon; Soo-Hyun Jung; Bumseok Kim; Sung-Dae Cho; Jeong-Seok Nam; Changsun Choi; Jeong-Hwan Che; Ji-Youn Jung (Food and Chemical Toxicology, 2023)

Efficient removal of chloroform from groundwater using activated percarbonate by cellulose nanofiber-supported Fe/Cu nanocomposites - Mingda Che; Jingzhe Xiao; Cancan Shan; Shaohuang Chen; Renliang Huang; Yitong Zhou; Mei Cui; Wei Qi; Rongxin Su (Water Research, 2023)

Toxicity evaluation of silica nanoparticles for delivery applications - Yue Tan; Dawei Yu; Jiayao Feng; Huimin You; Yan Bai; Jincan He; Hua Cao; Qishi Che; Jiao Guo; Zhengquan Su (Drug Delivery and Translational Research, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Seed priming with rutin enhances tomato resistance against the whitefly Bemisia tabaci - Juan Tang; Haowei Shen; Rong Zhang; Fengbo Yang; Jinyu Hu; Jinting Che; Hongyan Dai; Hong Tong; Qingjun Wu; Youjun Zhang; Qi Su (Pesticide Biochemistry and Physiology, 2023)

Mixed of arbor-shrub significantly enhanced the drought stress adaptive capacity of plantation forests—An interpretation based on dendroecology - Cunwei Che; Shengchun Xiao; Xiaomei Peng; Jingrong Su; Aijun Ding (Journal of Hydrology, 2023)

Adolescents’ use of influence tactics with parents in family travel decision making: A cross-societal comparison in Eastern Europe - Wen-Shen Yen; Che-Jen Su; Yi-Fang Lan; Marica Mazurek; Joanna Kosmaczewska; Biruta Švagždienė; Vitally Cherenkov (The Social Science Journal, 2023)

Tracing the future of epidemics: Coincident niche distribution of host animals and disease incidence revealed climate‐correlated risk shifts of main zoonotic diseases in China - Bo Cao; Chengke Bai; Kunyi Wu; Ting La; Yiyang Su; Lingyu Che; Meng Zhang; Yumeng Lu; Pufan Gao; Jingjing Yang; Ying Xue; Guishuang Li (Global Change Biology, 2023)
Climate has critical roles in the origin, pathogenesis and transmission of infectious zoonotic diseases. However, large‐scale epidemiologic trend and specific response pattern of zoonotic diseases under future climate scenarios are poorly understood. Here, we projected the distribution shifts of transmission risks of main zoonotic diseases under climate change in China. First, we shaped the global habitat distribution of main host animals for three representative zoonotic diseases (2, 6, and 12 hosts for dengue, hemorrhagic fever, and plague, respectively) with 253,049 occurrence records using maximum entropy (Maxent) modeling. Meanwhile, we predicted the risk distribution of the above three diseases with 197,098 disease incidence records from 2004 to 2017 in China using an integrated Maxent modeling approach. The comparative analysis showed that there exist highly coincident niche distributions between habitat distribution of hosts and risk distribution of diseases, indicating that the integrated Maxent modeling is accurate and effective for predicting the potential risk of zoonotic diseases. On this basis, we further projected the current and future transmission risks of 11 main zoonotic diseases under four representative concentration pathways (RCPs) (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) in 2050 and 2070 in China using the above integrated Maxent modeling with 1,001,416 disease incidence records. We found that Central China, Southeast China, and South China are concentrated regions with high transmission risks for main zoonotic diseases. More specifically, zoonotic diseases had diverse shift patterns of transmission risks including increase, decrease, and unstable. Further correlation analysis indicated that these patterns of shifts were highly correlated with global warming and precipitation increase. Our results revealed how specific zoonotic diseases respond in a changing climate, thereby calling for effective administration and prevention strategies. Furthermore, these results will shed light on guiding future epidemiologic prediction of emerging infectious diseases under global climate change.

Rab7a-mTORC1 signaling-mediated cholesterol trafficking from the lysosome to mitochondria ameliorates hepatic lipotoxicity induced by aflatoxin B1 exposure - Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Lin Che; Ting-Yu Li; Su-Min Mo; Dong-Bei Guo; Zhong-Ning Lin; Yu-Chun Lin (Chemosphere, 2023)

Efficient removal of Phaeocystis globosa from seawater with the persulfate activation by arbutin-modified cellulose nanocrystals - Mingda Che; Cancan Shan; Wenjie Zhang; Yanyi Duan; Renliang Huang; Mei Cui; Wei Qi; Rongxin Su (Chemosphere, 2023)

Associations between exposure to brominated flame retardants and metabolic syndrome and its components in U.S. adults - Zhiqiang Che; Huixun Jia; Renjie Chen; Keyu Pan; Zhe Fan; Chang Su; Zhenyu Wu; Tao Zhang (Science of The Total Environment, 2023)

Thermodegradation characterization of microplastics: Dispersion effect and pyrolysis kinetics by artificial intelligence - Wei-Hsin Chen; Shih-Che Sun; Jherwin B. Ocreto; Thanh-Binh Nguyen; Su Shiung Lam; Young-Kwon Park; Cheng-Di Dong (Chemical Engineering Journal, 2023)

Radial growth of Korshinsk peashrub and its response to drought in different sub-arid climate regions of northwest China - Cunwei Che; Shengchun Xiao; Xiaomei Peng; Aijun Ding; Jingrong Su (Journal of Environmental Management, 2023)

High chloroform removal using tannic acid to promote the activation of persulfate with Fe/Ni nanoparticles - Mingda Che; Zhiguo Chen; Sha Qiu; Mei Cui; Renliang Huang; Wei Qi; Zhimin He; Rongxin Su (Environmental Chemistry Letters, 2021)

Identification of Neuronal Polarity by Node-Based Machine Learning - Chen-Zhi Su; Kuan-Ting Chou; Hsuan-Pei Huang; Chiau-Jou Li; Ching-Che Charng; Chung-Chuan Lo; Daw-Wei Wang (Neuroinformatics, 2021)
Identifying the direction of signal flows in neural networks is important for understanding the intricate information dynamics of a living brain. Using a dataset of 213 projection neurons distributed in more than 15 neuropils of a Drosophila brain, we develop a powerful machine learning algorithm: node-based polarity identifier of neurons (NPIN). The proposed model is trained only by information specific to nodes, the branch points on the skeleton, and includes both Soma Features (which contain spatial information from a given node to a soma) and Local Features (which contain morphological information of a given node). After including the spatial correlations between nodal polarities, our NPIN provided extremely high accuracy (>96.0%) for the classification of neuronal polarity, even for complex neurons with more than two dendrite/axon clusters. Finally, we further apply NPIN to classify the neuronal polarity of neurons in other species (Blowfly and Moth), which have much less neuronal data available. Our results demonstrate the potential of NPIN as a powerful tool to identify the neuronal polarity of insects and to map out the signal flows in the brain’s neural networks if more training data become available in the future.

UBE2R2-AS1 Inhibits Xenograft Growth in Nude Mice and Correlates with a Positive Prognosis in Glioma - Wu Xu; Dan-dan Che; Liang Chen; Sheng-qing Lv; Jun Su; Jun Tan; Qing Liu; Ya-wen Pan (Journal of Molecular Neuroscience, 2021)

Efficient removal of chloroform in groundwater by polyethylene glycol-stabilized Fe/Ni nanoparticles - Huimin Si; Mingda Che; Zhiguo Chen; Sha Qiu; Mei Cui; Renliang Huang; Wei Qi; Zhimin He; Rongxin Su (Environmental Chemistry Letters, 2021)

Exploring the Deeper Crustal Structure Beneath the Tatun Volcanic Area, Taiwan - Chien-Min Su; Wei-Jhe Wu; Strong Wen; Yi-Heng Li; Yen-Che Liao; Wen-Yen Chang; Chau-Huei Chen (Pure and Applied Geophysics, 2021)

Maritimibacter harenae sp. nov. and Sneathiella litorea sp. nov.: members of Alphaproteobacteria isolated from sea sand - Shehzad Abid Khan; Hye Su Jung; Hye Yoon Park; Che Ok Jeon (Antonie van Leeuwenhoek, 2021)

Development of a region-partitioning method for debris flow susceptibility mapping - Shuang-shuang Qiao; Sheng-wu Qin; Jing-bo Sun; Wen-chao Che; Jing-yu Yao; Gang Su; Yang Chen; Uzodigwe Emmanuel Nnanwuba (Journal of Mountain Science, 2021)

Paenibacillus silvestris sp. nov., Isolated from Forest Soil - Jungeun Kim; Hye Su Jung; Ju Hye Baek; Byung Hee Chun; Shehzad Abid Khan; Che Ok Jeon (Current Microbiology, 2021)

Tannic acid enhances the removal of chloroform from water using NaOH-activated persulfate - Xudong Zhao; Zhiguo Chen; Mingda Che; Sha Qiu; Renliang Huang; Wei Qi; Zhimin He; Rongxin Su (Environmental Chemistry Letters, 2020)

A new technique for rapid assessment of eutrophication status of coastal waters using a support vector machine - Xianyu Kong; Xiaowei Che; Rongguo Su; Chuansong Zhang; Qingzhen Yao; Xiaoyong Shi (Journal of Oceanology and Limnology, 2018)

Distinct Histone Modifications Modulate DEFB1 Expression in Human Vaginal Keratinocytes in Response to Lactobacillus spp. - Jaehyouk Lee; Ara Jang; Jin Wook Kim; Jun Hyun Han; Byung Hee Chun; Hye Su Jung; Che Ok Jeon; Soon Chul Myung (Probiotics and Antimicrobial Proteins, 2017)

Effects of feeding rates on growth, feed utilization, and body composition of juvenile Pseudobagrus ussuriensis - Xianyong Bu; Xuqiu Lian; Ying Zhang; Chenghui Yang; Cunhe Cui; Jianfang Che; Baibing Tang; Baohui Su; Qicun Zhou; Yuhong Yang (Aquaculture International, 2017)

Effects of Porphyromonas gingivalis on Titanium Surface by Different Clinical Treatment - Nominzul Batsukh; Sheng Wei Feng; Wei Fang Lee; Sy-Jye Leu; Pei-Yo Tsai; Kuo-Ning Ho; Che Tong Lin; Ching-Hua Su; Wei-Jen Chang (Journal of Medical and Biological Engineering, 2017)

Identification and quantification of Cu-chlorophyll adulteration of edible oils - Mingchih Fang; Chia-Fen Tsai; Guan-Yan Wu; Su-Hsiang Tseng; Hwei-Fang Cheng; Ching-Hao Kuo; Che-Lun Hsu; Ya-Min Kao; Daniel Yang-Chih Shih; Yu-Mei Chiang (Food Additives & Contaminants Part B-Surveillance, 2015)

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite - Ya-Ting Chao; Chun-Lin Su; Wen-Han Jean; Wan-Chieh Chen; Yao-Chien Alex Chang; Ming-Che Shih (Plant Molecular Biology, 2014)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Halomonas cibimaris sp. nov., isolated from jeotgal, a traditional Korean fermented seafood - Sang Hyeon Jeong; Jong Hoon Lee; Ji Young Jung; Se Hee Lee; Moon Su Park; Che Ok Jeon (Antonie van Leeuwenhoek, 2013)

Preliminary evaluation of growth and conformation traits of local goats and Nubians upgraded by a black Boer line in Taiwan - An-Kuo Su; Shen-Suan Yang; Shui-Tsai Chen; Yu-Shin Cheng; Jan-Chi Huang; Ming-Che Wu; Jean-Paul Poivey (Tropical Animal Health and Production, 2012)

Induction of primitive pigment cell differentiation by visible light (helium–neon laser): a photoacceptor-specific response not replicable by UVB irradiation - Cheng-Che E. Lan; Shi-Bei Wu; Ching-Shuang Wu; Yi-Chun Shen; Tzu-Ying Chiang; Yau-Huei Wei; Hsin-Su Yu (Journal of Molecular Medicine, 2012)

A critical exploration of blood and environmental chromium concentration among oral cancer patients in an oral cancer prevalent area of Taiwan - Chi-Ting Chiang; Tsun-Kuo Chang; Yaw-Huei Hwang; Che-Chun Su; Kuo-Yang Tsai; Tzu-Hsuen Yuan; Ie-Bin Lian (Environmental Geochemistry and Health, 2011)

Reduction in arsenic intake from water has different impacts on lung cancer and bladder cancer in an arseniasis endemic area in Taiwan - Che-Chun Su; Jia-Ling Lu; Kuo-Yang Tsai; Ie-Bin Lian (Cancer Causes & Control, 2011)

ORIGINAL ARTICLE: Phylogeography of the giant wood spider ( Nephila pilipes , Araneae) from Asian–Australian regions - Yong‐Chao Su; Yung‐Hau Chang; Sin‐Che Lee; I‐Min Tso (Journal of Biogeography, 2007)
Aim There are currently few population genetic studies on widely distributed SE Asian terrestrial organisms. We have studied the genetic diversification pattern of the giant wood spider, Nephila pilipes (Araneae: Tetragnathidae) to see whether fluctuations in rain forest extents generated by Quaternary climatic changes left signatures on populations of this agile terrestrial arthropod. Location The collecting localities were distributed in the following seven regions: (1) N Australia; (2) India (Calcutta, Karziranga and Sukna); (3) SE Asia (N Vietnam, Malaysia, Singapore and Bali); (4) SE China (Fujian, Guandong, Hong Kong and Hainan); (5) SW China (Guangxi and Yunnan); (6) E Asian islands (Ryukyu islands and Taiwan); and (7) the Philippine Islands. Methods A total of 374 specimens were collected from the East Asian continent and islands, SE Asia, India, and northern Australia. Mitochondrial cytochrome oxidase I gene partial sequences were used as the molecular marker to infer the phylogeographic diversification patterns. Results From the specimens collected, 67 haplotypes were identified, which could be grouped into five major clades. The dominant clade contained populations in regions ranging from Okinawa to Bali (spanning a distance of more than 4000 km), but their genetic variations were not structured and were not significantly associated with geographical distances. Three clades contained specimens collected from peripheral regions of the distribution range of N. pilipes , such as India, N Australia, and NE Asia. Members of the clade distributed in NE Asia were sympatric but those of the clades distributed in Australia and India were allopatric with those of the dominant clade. Main conclusions The results of this study indicate that, during Quaternary glacial periods, the rain forests in SE Asia might have been more or less continuous and thus generated an unstructured genetic diversification pattern of N. pilipes inhabiting this region. However, during such periods, populations in peripheral regions such as India, N Australia and NE Asia might have been isolated in refugia, thus accounting for the observed genetic divergence from populations in the SE Asian region.

Characterization of Symbiobacterium toebii , an obligate commensal thermophile isolated from compost - Sung-Keun Rhee; Che Jeon; Jin-Woo Bae; Kwang Kim; Jae Song; Joong-Jae Kim; Seung-Goo Lee; Hong-Ik Kim; Seung-Pyo Hong; Yoon-Ho Choi; Su-Mi Kim; Moon-Hee Sung (Extremophiles, 2002)